Osteoporotic Fractures of the Thoracic and Lumbar Vertebrae: Diagnosis and Conservative Treatment - Spiegl, Ulrich; Bork, Hartmut; Gruninger, Sebastian; Maus, Uwe; Osterhoff, Georg; Scheyerer, Max J.; Pieroh, Philipp; Schnoor, Jorg; Heyde, Christoph-Eckhard; Schnake, Klaus J. (Deutsches Ärzteblatt international, 2021)
Background: The prevalence of osteoporotic vertebral body fractures in Europe is 18-26%. Although most of these injuries can be treated conservatively, the underlying concepts have not been defined clearly or uniformly. In this article, we present the current state of the evidence on the diagnosis and conservative treatment of osteoporotic fractures of the thoracic and lumbar vertebrae. Methods: A systematic review of the literature up to May 2020 was carried out in the PubMed and Web of Science Core Collection databases. 549 articles were identified, of which 36 were suitable for inclusion in the review. Articles were sought in the areas of diagnosis, provision of physical aids, pharmacotherapy, physiotherapy, and treatments from the realm of alternative medicine. Results: The primary diagnostic technique was conventional x-ray in two planes (with the patient standing, if possible), which had 51.3% sensitivity and 75% specificity. If a fracture was suspected, magnetic resonance imaging (MRI) of the entire spine and regional computed tomography (CT) were carried out. The overall state of the evidence on treatment is poor; the best available evidence is for exercise therapy and physiotherapy, which are supported by three level I and four level II studies. Improvements were seen mainly in mobility and a reduced fear of falling. The use of an active orthosis can be useful as well. No evidence was found on the use of drugs or alternative medicine exclusively in the conservative treatment of osteoporotic vertebral body fractures. Conclusion: It is reasonable to evaluate instability with imaging repeatedly, at regular intervals, over a period of six months. There is still a lack of reliable data on the optimal intensity and duration of physiotherapy, and on the use of orthoses.
CRIS-Team WoS Importer:2022-01-21